Arthroscopic Biceps Tenodesis With Interference Screw Fixation: A Technique Video - Brian Forsythe MD; Vahram Gamsarian BE; Harsh H. Patel BA; Elyse Berlinberg BS; Alec Warrier BS; Haseeb Goheer BS; Vikranth Mirle BS; Lashmanan Sivasundaram MD; Christopher M. Brusalis MD (SAGE Publishing, 2024)
Background: Management of long head of the biceps tendon (LHBT) pathology is accomplished through a biceps tenotomy or tenodesis. While both modalities provide beneficial outcomes, a biceps tenodesis may confer improved cosmesis, functional outcomes, and decreased muscle cramping postoperatively. Many procedural considerations are undertaken prior to a tenodesis, such as the surgical approach and fixation device. While similar clinical outcomes are achieved between an open subpectoral and arthroscopic suprapectoral biceps tenodesis (ASPBT) with interference screw (IS) fixation, the latter technique offers a minimally invasive modality. Indications: The primary indications for an ASPBT include superior labrum anterior posterior (SLAP) tears, LHBT tears, biceps instability, bicipital tunnel disease, biceps pulley lesions, and biceps tenosynovitis. Contraindications to the arthroscopic approach include a distal lesion of the biceps tendon below the pectoralis major tendon (PMT). The IS may be used to create a biomechanically stiffer construct. Technique Description: With the arthroscope in the lateral portal, the distal aspect of the bicipital groove proximal to the superior border of the PMT is identified and opened. The LHBT is subsequently mobilized and released. An anterosuperolateral portal is localized with a spinal needle positioned perpendicular to the bicipital tunnel, 1.5 cm proximal to the superior border of the PMT. The biceps is then removed ex vivo and whip-stitches are sewn beginning 1 cm proximal to the myotendinous junction of the LHBT. After firmly associating the LHBT with the tip of the IS, a guidewire is placed 1.5 cm superior to the superior border of the PMT, perpendicular to the humerus, and a reamer is used to prepare a 6-, 7-, or 8-mm diameter socket. The tendon is inserted through the accessory portal into the tunnel, followed by screw fixation. Suture tails are tied with 5 alternating half hitches, each secured via an arthroscopic knot pusher. Results: ASPBT with IS fixation provides significant pain relief, improves range of motion (ROM), and enhances quality of life. Discussion: ASPBT with IS fixation provides significant improvements in patient-reported and functional outcomes and thus can be an acceptable treatment for LHBT pathology. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.